MANAJEMEN `USTÄÅ¼ DAN `USTÄÅ¼AH DI PESANTREN MODERN - Ulfa, Maria; Irawan, Irawan (Madrasa: Journal of Islamic Educational Management, 2018)
The target of managing `ust?? (Islamic Educators) at the Ummul Quro Al-Islami, Modern Islamic Boarding School (PMUQI) is not clearly defined. Teachers who teach are often not in accordance with postgraduate qualifications. Teacher salaries are often deducted. This study aims to reveal the processes of recruitment, selection, placement, training, assessment and salary/compensation of educators in PMUQI Bogor, West Java, Indonesia. The research method used is a qualitative method. The results of the study show that (1) the recruitment of educators always considers the increase in the number of santri and the number of classes each year, prioritizing alumni; (2) selection is done by collecting administrative files and interviews. There is no test in the selection of teaching staff; (3) placement non test is adjusted to educational qualifications and the ability of educators; (4) training and development are carried out in Islamic boarding schools and madrasas; (5) performance appraisal is carried out by establishing an Honorary Board of Teachers (HBT) and giving performance assessment report cards from foundations and pesantren, (6) giving salary to educators based on length of service, structural positions, teaching hours and educational qualifications.